Karakteristik dan Kebijakan Dividen Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Soliyah Wulandari (Department of Accounting-Faculty of Economic and Business (FEB), 2020)
The aim of this research is to prove empirically the influence of firm characteristics. There are market price to book value ratio, firm age, market capitalization, debt equity ratio, earnings per share, liquidity, and growth of asset as firm characteristics. The research object are manufacture firm in Indonesian Stock Exchange during 2013-2017. The sample selection is using purposive sampling method. Based on criteria, samples which are used in this research are 37 firms. Secondary data are collected with documentation of financial statement from Indonesia Stock Exchange. Those data are processed using statistical test of multiple regressions. The result of this research proves that market price to book value ratio, debt equity ratio, earnings per share, and growth influence to dividend policy. In the other hand, firm age, market capitalization, and liquidity influence to dividend policy.